Development and application of asymmetric C-N bond formation - Snell, R (2011)
A synthetic investigation on the chemistry of cyclotryptamine derived natural products, with a particular focus on the synthesis of the trimeric-alkaloid, hodgkinsine. Methodology has been developed to tackle this complex natural product which utilises a desymmetrization approach; this strategy hinges on the development and applications of asymmetric C-N bond forming reactions. Chapter one examines elements of symmetry in natural products, looking in particular at the synthesis of compounds which contain cyclotryptamine functionality. Chapter two contains a brief review of enantioselective desymmetrization paying attention, if possible, on its application in the synthesis of natural products. In the remaining chapters we discuss our own progress and results in our pursuit of an efficient enantioselective total synthesis of hodgkinsine.